Hagiographic Materia Medica - Fraser, Peter (Homœopathic Links, 2018)
The medieval practice of invoking the intercession of particular Saints bears a fundamental similarity to the principles of homeopathy. The Golden Legend ‘Lives of the Saints’ is akin to our Materia Medica. Some remedy pictures connect to a Saint's story and understanding that story helps in understanding the remedy.
Keywords: Hagiography; Saints; LSD; Secale cornutum; Actaea spicata; Ignis alcoholis